THE APPLICATION OF SCIENTIFIC APPROACH IN TEACHING READING COMPREHENSION FOR THE TENTH GRADE STUDENTS OF SMA PABA BINJAI - Sonia Nurul Fadhilah; Siti Aisah Ginting (Universitas Negeri Medan, 2021)
This study was aimed to analyzing how the teacher apply the scientific approach in teaching reading comprehension for the tenth grade students of SMA PABA Binjai and to find out the difficulties faced by the English teacher in teaching learning process using scientific approach in 2013 curriculum. This study was conducted by using descriptive qualitative research design. The data sources of the research were the English teacher of SMA PABA Binjai. The techniques of collecting data were observation and interview. The findings showed that there was only one step of Scientific Approaches used in teaching process. Afterward, that was three difficulties faced by the teacher related to the application of 2013 Curriculum; (a) teacher faced difficulties in student’s readiness. Students were not actively participated in the classroom; (b) teacher faced difficulties in the assessment, (c) teacher faced difficulties in the steps of Scientific Approach could not apply in one meeting. The teacher was not able to manage the time when using the scientific approach. All teachers must be prepared by the government by giving them some teaching practice and training related to the application of 2013 Curriculum.Keywords: Scientific Approach, Teaching Reading Comprehension, 2013 Curriculum.